SCARCITY MARKETING TO PERCEIVED UNIQUENESS AND DESIRABILITY USERS OF THE FOOD DELIVERY SERVICE INDONESIA APPLICATION - Nafarin, Lydia; Oktavio, Adrie (Jurnal Aplikasi Manajemen, 2021)
The number of online applications users of food and beverage delivery services in Indonesia is growing every year. That is also followed by many culinary entrepreneurs who have established partnerships with online applications. One of the major online food and beverage delivery service applications in Indonesia is Grabfood. Through Grabfood, products ordered online by users will be delivered to their homes in a relatively short time. Ordering food and drinks through Grabfood is also very beneficial for users because they can enjoy a variety of attractive promotions, both in the form of food and beverage discounts, cashback, shipping cost discounts, and so on. One of the promotional strategies carried out by Grabfood is to do scarcity marketing. This study aims to observe whether the scarcity marketing carried out by Grabfood can affect the desirability of Grabfood users and at the same time examine the role of perceived uniqueness as an intervening variable in the model developed by this study. Scarcity marketing in the study is divided into two types, namely limited-quantity scarcity and limited-time scarcity. The sample in this study involved one hundred and thirteen active users of the Grabfood application who have filled out a complete online questionnaire. The data processing results show that limited-quantity scarcity and limited-time scarcity can directly have a positive and significant effect on perceived uniqueness and desirability. Furthermore, perceived uniqueness also has a direct positive and significant effect on desirability. In its position as an intervening variable, the construct of perceived uniqueness can partially mediate the relationship between limitedquantity scarcity and limited-time scarcity on desirability. Further research focused on another intervening variable that partially mediates the relationship between limited-quantity scarcity and limited-time scarcity to desirabilities, such as perceived value or social status.